TRPA1 mediates formalin-induced pain - McNamara, Colleen R.; Mandel-Brehm, Josh; Bautista, Diana M.; Siemens, Jan; Deranian, Kari L.; Zhao, Michael; Hayward, Neil J.; Chong, Jayhong A.; Julius, David; Moran, Magdalene M.; Fanger, Christopher M. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
The formalin model is widely used for evaluating the effects of analgesic compounds in laboratory animals. Injection of formalin into the hind paw induces a biphasic pain response; the first phase is thought to result from direct activation of primary afferent sensory neurons, whereas the second phase has been proposed to reflect the combined effects of afferent input and central sensitization in the dorsal horn. Here we show that formalin excites sensory neurons by directly activating TRPA1, a cation channel that plays an important role in inflammatory pain. Formalin induced robust calcium influx in cells expressing cloned or native TRPA1 channels, and these responses were attenuated by a previously undescribed TRPA1-selective antagonist. Moreover, sensory neurons from TRPA1-deficient mice lacked formalin sensitivity. At the behavioral level, pharmacologic blockade or genetic ablation of TRPA1 produced marked attenuation of the characteristic flinching, licking, and lifting responses resulting from intraplantar injection of formalin. Our results show that TRPA1 is the principal site of formalin's pain-producing action in vivo, and that activation of this excitatory channel underlies the physiological and behavioral responses associated with this model of pain hypersensitivity.
Gesehen am 06.12.2021